Model for the transmission of HIV in a population with differentiation of sexes and uses of preventive measures - Toro-Zapata, Hernán Dario (2018)
A model based on ordinary differential equations to describe the dynamics of HIV transmission, considering differentiation in the population according to gender and sexual orientation is proposed, in order to analyze the impact of preventive measures in reducing HIV transmission. A numerical study is carried out to illustrate different control scenarios through preventive measures